2018
DOI: 10.1016/j.rmed.2018.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Can the ceramic industry be a new and hazardous sector for work-related asthma?

Abstract: The results demonstrate that besides the sectors known to cause WRA, ceramic and metal industries can be related to important exposures related to WRA. Medical surveillance of employees in this sector is important in early detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
4
0
2
Order By: Relevance
“…Besides, NPs size distribution showed a predominant size range from 2 nm to 650 nm in particulate matter with variable composition from a high traffic area [52]. Inorganic agents of a refractory nature can cause respiratory diseases due to their accumulation in the lungs [53,54]. It has been reported that exposure to traffic pollution (including NPs) is related to neurodevelopmental and neurodegenerative diseases [55].…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Besides, NPs size distribution showed a predominant size range from 2 nm to 650 nm in particulate matter with variable composition from a high traffic area [52]. Inorganic agents of a refractory nature can cause respiratory diseases due to their accumulation in the lungs [53,54]. It has been reported that exposure to traffic pollution (including NPs) is related to neurodevelopmental and neurodegenerative diseases [55].…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…The finest fractions (with aerodynamic particle diameter Dp ≤ 2.5 µm) are considered the most harmful for human health (Gakidou et al, 2017;Landrigan et al, 2017;World Health Organization, 2016). In workplace settings, ceramic industry workers are known to suffer from work-related asthma due to airborne dust inhalation (Kurt et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed that WRA cases are increasingly diagnosed in some industries or occupations. [8][9][10][11][12][13] Immunological evaluation of work-related allergens has proven useful in demonstrating WRA.…”
mentioning
confidence: 99%